Gila monster (Heloderma suspectum) envenomation: Descriptive analysis of calls to United States Poison Centers with focus on Arizona cases. (January 2015) - French, Robert; Brooks, Daniel; Ruha, Anne-Michelle; Shirazi, Farshad; Chase, Peter; Boesen, Keith; Walter, Frank
Abstract Background. The Gila monster (Heloderma suspectum) is a venomous lizard native to the deserts of southwestern United States (US) and northern Mexico. The purpose of this study was to describe human exposures to Gila monsters reported to US poison control centers (PCCs) with a focus on Arizona cases. Methods. The American Association of Poison Control Centers' National Poison Data System (NPDS) was used to access and retrospectively review all calls to US PCCs, concerning Gila monsters between January 1, 2000 and October 31, 2011. In addition, detailed records from the two Arizona PCCs were reviewed for the same time period. Results. A total of 319 calls regarding Gila monsters were identified in the NPDS. Of these, 105 (33%) were human exposures; most (79%) occurred in males. A total of 71 (68%) of these 105 cases were referred to a health care facility (HCF); 30 (29%) were managed on-site. Of the 71 HCF referrals, 36 (51%) were discharged home and 17 (24%) were admitted. Most (65%) admissions were to an intensive care unit (ICU). Arizona's PCCs received 70 unique reports of Gila monster bite. Most (77%) of the bites in Arizona involved an upper extremity. Eight (11%) involved patients under the age of 18 years. Eleven (16%) Arizona cases were work-related. Twenty-eight (40%) of the 70 bites in Arizona were evaluated in a HCF, but not admitted. Eleven (16%) were admitted, of which five were to an ICU. Six patients had edema of airway structures; three required emergent airway management, one by cricothyrotomy. There were no deaths. Conclusion. Gila monster bites are uncommon. Many cases did not require hospitalization. Edema of airway structures is an infrequent, but life-threatening complication.